Mechanistic link between β barrel assembly and the initiation of autotransporter secretion - Pavlova, Olga (National Academy of Sciences, 2013)
Autotransporters are bacterial virulence factors that contain an N-terminal extracellular (“passenger”) domain and a C-terminal β barrel (“β”) domain that anchors the protein to the outer membrane. The β domain is required for passenger domain secretion, but its exact role in autotransporter biogenesis is unclear. Here we describe insights into the function of the β domain that emerged from an analysis of mutations in the Escherichia coli O157:H7 autotransporter EspP. We found that the G1066A and G1081D mutations slightly distort the structure of the β domain and delay the initiation of passenger domain translocation. Site-specific photocrosslinking experiments revealed that the mutations slow the insertion of the β domain into the outer membrane, but do not delay the binding of the β domain to the factor that mediates the insertion reaction (the Bam complex). Our results demonstrate that the β domain does not simply target the passenger domain to the outer membrane, but promotes translocation when it reaches a specific stage of assembly. Furthermore, our results provide evidence that the Bam complex catalyzes the membrane integration of β barrel proteins in a multistep process that can be perturbed by minor structural defects in client proteins.